1990
DOI: 10.1093/infdis/161.6.1153
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Morphology of Staphylococci on Memphis Agar: Phase Variation of Slime Production, Resistance to  -Lactam Antibiotics, and Virulence

Abstract: The growth of Staphylococcus epidermidis sensu stricto and Staphylococcus saprophyticus on Memphis agar yielded up to 6 morphotypes with each strain. With S. epidermidis, one morphotype produced slime (rho) but became non-slime-producing (epsilon) at a high frequency. The slime-producing rho variants were methicillin-resistant and more virulent than methicillin-susceptible epsilon variants in an endocarditis model. With S. saprophyticus, phase variation was of higher frequency. Nitrosoguanidine mutagenesis pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 34 publications
5
62
0
Order By: Relevance
“…As outlined by Christensen et al (1990), a spectrum of phenotypic variants with differing levels of biofilm production was isolated from an IS256-positive strain, RP62A, on Memphis agar. To see whether a similar spectrum could be isolated from strains of S. epidermidis that lacked IS256, four S. epidermidis isolates were further characterized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined by Christensen et al (1990), a spectrum of phenotypic variants with differing levels of biofilm production was isolated from an IS256-positive strain, RP62A, on Memphis agar. To see whether a similar spectrum could be isolated from strains of S. epidermidis that lacked IS256, four S. epidermidis isolates were further characterized.…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcal strains used in the study are shown in Table 1. Ability to form a biofilm (crusty phenotype on CRA, (Christensen et al, 1990). All isolates were found to be divergent as assessed by PFGE (methods described below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm Formation Assay-As previously described, the microtiter plate test was used to quantify the biofilm (39,40) with slight modifications. Briefly, overnight culture of S. epidermidis strains in BM medium was diluted 1:100 in fresh BM and grown with aeration at 37°C for 12 h. The culture was further diluted in fresh TSB to A 600 of 0.01 and then inoculated into a sterile 96-well polystyrene microtiter plates (200 l/well).…”
Section: Rna Isolation and Quantitative Real Time Rt-pcr (Qrt-pcr)-totalmentioning
confidence: 99%
“…Role of AbfR in Biofilm Formation-To examine whether AbfR modulates biofilm formation in S. epidermidis, we performed a semiquantitative adherence assay as previously described (39,40,42). As shown in Fig.…”
Section: Journal Of Biological Chemistry 3747mentioning
confidence: 99%